Scar formation and patient satisfaction after thyroidectomy with and without surgical drains - Kim, Hyo Young; Kim, Ho Seong; Kim, Hong Il; Park, Jin Hyung; Yi, Hyung Suk (International Surgery Journal, 2019)
Background: Several comparative studies have documented the outcomes of negative pressure drain use after thyroidectomy. However, these previous studies did not focus on scar formation. The aim of this study was to compare thyroidectomy outcomes with and without negative pressure drain use in terms of scar formation. Methods: Nine hundred seventy-five patients who underwent thyroidectomy between January 2012 and December 2013, at Kosin University Gospel Hospital were enrolled in this study. Patients were assigned to one of two groups at the surgeon's discretion: the negative pressure drain group (n=515) or the no drain group (n=460). Medical records were reviewed, and the incidence and severity of scar formation were compared. We estimated patient satisfaction seven months postoperatively based on aesthetic and functional outcomes using the patient and observer scar assessment scale. Results: The incidence of mild scarring was higher in the no drain group, but this difference was not statistically significant (p=0.069). The incidence of severe scarring was significantly higher in the negative pressure drain group (5.83%, p<0.001). Based on the patient and observer scar assessment scale data from 205 patients, patient satisfaction was significantly higher in the no drain group (p=0.006). Itching was reported significantly less frequently in the no drain group (p=0.034). There were no significant differences between groups with respect to pain or observer scar scale score. Conclusions: This study suggests that not using a drain after thyroidectomy leads to high patient satisfaction and reduces the likelihood of severe scar formation.